2000
DOI: 10.1359/jbmr.2000.15.10.2052
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Pamidronate for Treatment of Reflex Sympathetic Dystrophy During Breast Feeding

Abstract: A 39-year-old woman presented in the first month of pregnancy with reflex sympathetic dystrophy involving both lower legs. Symptoms became so severe that she could not walk unassisted, and the pain worsened after delivery. Radiographs showed patchy reduction in apparent density in the tarsal bones and around the ankles and knees. Uptake was increased in these areas on technetium methylene diphosphonate bone scan. Bone density (dual-energy X-ray absorptiometry) was reduced in the spine, hip, and radius. Biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 19 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…Painful traumatic rib fractures commonly cause chest morbidity; non-steroidal anti-inflammatory and opioid drugs form the mainstay of treatment but may cause toxicity. The British Thoracic Society recommends using ultrasound to localise interpleural procedure insertion points [3] and National Institute for Health and Clinical Excellence suggests ultrasound improves efficacy and safety in regional nerve blockade [4]. Our use of real-time in-plane ultrasound guidance complies with both and improves the safety of this analgesic technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Painful traumatic rib fractures commonly cause chest morbidity; non-steroidal anti-inflammatory and opioid drugs form the mainstay of treatment but may cause toxicity. The British Thoracic Society recommends using ultrasound to localise interpleural procedure insertion points [3] and National Institute for Health and Clinical Excellence suggests ultrasound improves efficacy and safety in regional nerve blockade [4]. Our use of real-time in-plane ultrasound guidance complies with both and improves the safety of this analgesic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30 g calcium is transferred from mother to fetus during pregnancy [3]. Compensatory mechanisms restore calcium deficit with reductions in bone mineral density [3,4] and support advice to stop breastfeeding in clinically apparent osteoporosis [3]. Acute pain services have a small presence on obstetric wards but early referrals are recommended with escalating opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…The baby remained healthy and presented normal growth. 23 In addition, in the case of the patient suffering from Gaucher's disease mentioned above, breastfeeding for 1 year was not accompanied by adverse effects to the infant's health and developmental rate. 17 In the report of 4 cases by Chan et al, also described above, women received intravenous pamidronate for 19-46 months before conception and all of them breastfed their babies for 6 weeks to 18 months.…”
Section: B Bps and Lactationmentioning
confidence: 98%
“…Although bisphosphonates are known to cross the placental barrier and may have an effect on fetal serum calcium levels and growth there have been no reports of congenital abnormalities associated with use of bisphosphonates in animal teratology studies [13]. Concerning bisphosphonates therapy during breastfeeding, a study showed that pamidronate is undetectable in breast milk of nursing mothers in the first 48 h after a 30 mg infusion [14]. In our case, we decided to postpone the bisphosphonate therapy after the C-section and, in accordance with the patient, to suspend breastfeeding in order to avoid further bone demineralization.…”
Section: P Sachsanidis Et Al Open Journal Of Obstetrics and Gynecologymentioning
confidence: 99%